On Re-enacting a Hotel Space - Licha, Emanuel (Intermédialités / Intermediality)

(untitled) (Revue intermédialités (Presses de l’Université de Montréal), 2016)
The presence of a hotel for journalists in a US Army training facility prompted the research on “war hotels” used by media workers when they cover a conflict. One of the results of this research is a feature-length film titled Hotel Machine, which was shot in the post-conflict environment of five hotels situated in Sarajevo, Belgrade, Beirut, Gaza, and Kiev. The various techniques used in the film to “make the hotel speak” are discussed in this essay.